2008
DOI: 10.1002/dmrr.814
|View full text |Cite
|
Sign up to set email alerts
|

Hypouricemia linked to an overproduction of nitric oxide is an early marker of oxidative stress in female subjects with type 1 diabetes

Abstract: Oxidative stress is already present in the early stages of type 1 diabetes. We conclude that the initial increase in oxidative stress could be linked to a reduction in plasmatic levels of uric acid, which is probably directly caused by an overproduction of NO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…There is evidence that diabetes compromises these desirable effects presumably because the overabundance of the superoxide anion inactivates NO by converting it to peroxynitrite, which, in turn, is broken down to nitrate, nitrite and oxygen [9,11]. This is consistent with the animal studies [5] and clinical data just reviewed which have shown that the NOx is increased in patients with diabetes [15,29]. How can NO be both excessive and deficient?…”
Section: Nitrosative Stress In Diabetessupporting
confidence: 58%
See 4 more Smart Citations
“…There is evidence that diabetes compromises these desirable effects presumably because the overabundance of the superoxide anion inactivates NO by converting it to peroxynitrite, which, in turn, is broken down to nitrate, nitrite and oxygen [9,11]. This is consistent with the animal studies [5] and clinical data just reviewed which have shown that the NOx is increased in patients with diabetes [15,29]. How can NO be both excessive and deficient?…”
Section: Nitrosative Stress In Diabetessupporting
confidence: 58%
“…We also measured urate in our longitudinal study of diabetes, and demonstrated that it was decreased by 25% in early type 1 diabetes (Table 1). Moreover, we and Pitocco [29] documented a negative correlation between urate and glycosylated hemoglobin which indicates that the suppression of the former is a compensatory response to hyperglycemia related oxidative stress. Peroxynitrite is the major oxidant which reacts with urate, but the superoxide anion and hydrogen peroxide can also do so, but they are not as potent oxidizers as is peroxynitrite [31].…”
Section: Oxidative Stress and Autonomic Nerve Function In Early Diabetesmentioning
confidence: 58%
See 3 more Smart Citations